Effects of a wearable hand orthosis on upper and lower limb motor recovery in stroke patients: a randomized controlled trial - Xu, Lijuan; Zhang, Jie; Liu, Qiang; Cao, Yefan; Aizezi, Nazhakaiti; Tian, Jing; Wu, Cheng; Fang, Liyu; Chen, Liyi; Zhang, Yanzheng; Pang, Xueming; Lin, Yanli; et al. (Frontiers in Bioengineering and Biotechnology, 2025)
ObjectiveOrthoses have shown potential in addressing upper limb spasticity in stroke survivors; however, their influence on motor recovery remains controversial. This study aimed to examine the effects of a wearable hand orthosis on spasticity, motor recovery of both upper and lower limbs, balance, and activities of daily living in stroke.DesignRandomized controlled trial.SettingInpatient rehabilitation department.ParticipantsFifty-one stroke survivors with hemiplegia were randomly assigned to either an experimental group (n = 26) or a control group (n = 25).InterventionsBoth groups underwent a 4-week conventional rehabilitation program. Participants in the experimental group engaged in a self-directed training program utilizing a wearable hand orthosis for 5 h daily, whereas the control group followed the identical regimen without the use of the orthosis.Outcome MeasuresModified Ashworth Scale (MAS) for spasticity, Fugl-Meyer Assessment for upper and lower extremities (FMA-UE & FMA-LE), Berg Balance Scale (BBS) and Barthel Index (BI).ResultsThe experimental group showed greater improvements in FMA-UE (difference = 4.37, P = 0.022), BBS (difference = 12.37, P < 0.001), and BI (difference = 17.65, P < 0.001) compared to the control group. No significant differences were found in MAS (P = 0.654) or FMA-LE (P = 0.495). A stepwise multiple linear regression analysis revealed that improvement in FMA-UE was a significant predictor of BBS recovery in the experimental group (r2 = 0.207, P = 0.022).ConclusionThe use of a wearable hand orthosis in self-directed training significantly improved upper limb motor recovery, balance, and ADL abilities in stroke survivors. The observed correlation between upper limb recovery and balance improvement indicates the potential of this orthosis to facilitate comprehensive rehabilitation.